Hygroscopic Expansion of Aesthetic Restorative Materials: One-Year Report - S. Emamieh; A. Ghasemi; H. Torabzadeh (Tehran University of Medical Sciences, 2011)
Objective: To measure the long-term linear hygroscopic expansion (LHE) of several materials using bulked and layered techniques. Materials and Methods: Seven materials were used; Fuji Cap II, Fuji II LC, Photac-Fil Aplicap, Vitremer, Dyract, Tetric and Z100. Ten specimens (6×4 mm) were made for each material using layered and bulked techniques (each group comprises five specimens). The specimens were stored in distilled water at 37°C. The length of each specimen was measured immediately after preparation, 24 hours, one week, one month, three months, six months, nine months and one year. This was used to calculate the percentage change in the length of materials. The mean LHE and standard deviation were calculated. Repeated measure analysis and paired sample t-test were used. Results: The type of material and time had a significant effect on LHE. Fuji Cap II and Fuji II LC exhibited no significant changes after one-year and one month, respectively. However, layered specimens of Photac-Fil Aplicap and Tetric showed constant expansion until six month, whereas bulked specimens reached the constant length at three months. Constant expansion was obtained for layered and bulked specimens of Dyract and Z100 at six month. Layered specimens of Vitremer showed no significant differences except between 24 hours and one year measurements. But in bulked specimens, the results at nine months and one year were significantly different from those obtained at three months and before. Conclusion: Fuji II showed no significant LHE and resin-modified glass ionomer cements (RMGICs) exhibited the highest LHE. Dyract maintained an intermediate LHE in comparison with RMGIC and composite resin.